2021
DOI: 10.1021/acsami.0c21321
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Controlled Construction of Fe–Nx Active Sites on the Edge of a Graphene Nanoribbon for an Electrocatalytic Oxygen Reduction Reaction

Abstract: Pyrolytically prepared iron and nitrogen codoped carbon (Fe/N/C) catalysts are promising nonprecious metal electrocatalysts for the oxygen reduction reaction (ORR) in fuel cell applications. Fabrication of the Fe/N/C catalysts with Fe−N x active sites having precise structures is now required. We developed a strategy for thermally controlled construction of the Fe−N x structure in Fe/N/C catalysts by applying a bottom-up synthetic methodology based on a N-doped graphene nanoribbon (N-GNR). The preorganized aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The rate of coverage change constitutes the coupled differential equations. The rate of change is defined as (10) θ i is the fractional coverage of species i, n j is the number of adsorbate i being consumed (−) or produced (+) in step-j, and r j is the step-j where species i is involved. The set of coupled differential equations was computed numerically until a steady state is reached.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rate of coverage change constitutes the coupled differential equations. The rate of change is defined as (10) θ i is the fractional coverage of species i, n j is the number of adsorbate i being consumed (−) or produced (+) in step-j, and r j is the step-j where species i is involved. The set of coupled differential equations was computed numerically until a steady state is reached.…”
Section: Introductionsupporting
confidence: 87%
“…In recent years, various methods have been proposed to engineer the active site structures and to enhance the ORR activity of pyrolyzed Fe-N-C catalysts . Among them is by dispersing the FeN 4 active site near the graphitic edges (FeN 4 -edge) of the catalyst. In 2020, Ma et al reported a combined experimental and theoretical study discussing the ORR activity of a pyrolyzed Fe-N-C catalyst with abundant graphitic edges . This catalyst is reported to have excellent ORR activity and durability, rivaling that of the Pt/C catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] XPS analysis shows the existence of Fe-N in p-FeP/NCF/CP, which may also contribute and facilitate the activity of the catalyst. 26,[32][33][34][35][36] Therefore, the 3D network and porous structure of p-FeP/NCF/CP endows its advantages of exposing more active sites for HER, and the low crystallinity and the existence of Fe-N collectively account for its high catalytic activity toward HER.…”
Section: Electrocatalytic Activity For Hermentioning
confidence: 99%
“…The application possibilities listed above have been discussed in this review. Particular attention is paid to nanographenes, including functionalized and heteroatoms-doped ones, which preparation and new applications constitute a “hot topic” in science and technology [ 6 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Currently, only bottom-up methods, where nanographene is constructed from smaller entities by stepwise organic synthesis, allow the preparation of nanographenes, including functionalized and doped ones, with perfect control of shapes and sizes and, therefore, perfectly defined properties [ 2 , 5 , 6 , 11 , 12 ,…”
Section: Introductionmentioning
confidence: 99%
“…It should be added that nanographenes (graphenoids), obtained via reactions discussed in this review, can be planar or otherwise distorted, that is, non-planar, one- (1D), two- (2D), and three-dimensional (3D) [ 6 , 11 , 12 , 17 , 23 , 24 , 25 , 26 , 36 , 38 , 40 , 43 , 46 , 47 , 49 , 52 ]. Graphenoids with planar sheets of varying size, shape, and periphery have made great progress in practical applications of electronics, energy storage, catalysis, and biosensing [ 6 , 11 , 12 , 14 , 15 , 16 , 17 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 47 , 50 , 52 , 53 ]. In recent years, a growing number of graphenoid studies have focused on unusual curved and warped stru...…”
Section: Introductionmentioning
confidence: 99%